Hair-follicle transplant as chronic skin ulcer treatment - Silva,Leandro (2022)
Abstract Chronic skin ulcers treatment is a common challenge in clinical dermatology practice. In recent years, hair-follicles transplantation emerged as an effective chronic skin ulcer treatment. The healing improvement is probably due to the action of follicle stem cells. We present a case of a chronic skin ulcer due to livedoid vasculopathy that fully healed 2 months after hair-follicle implantation into the wound bed.